Apresente uma derivação à extrema direita (DED) da sentença A := A * (B + (C * A)) sobre a gramática a seguir (Sebesta, 2000).
G = ({atr, exp, id}, {A, B, C, :=, +, *, (, )}, P, atr)
P = {< atr > -> < id > := < exp >
< exp > -> < id > + < exp > | < id > * < exp > | ( < exp > ) | < id >
< id > -> A | B | C }
< atr >
< id > := < exp >
< id > := < id > * < exp >
< id > := < id > * ( < exp > )
< id > := < id > * ( < id > + < exp > )
< id > := < id > * ( < id > + ( < exp > ) )
< id > := < id > * ( < id > + ( < id > * < exp > ) )
< id > := < id > * ( < id > + ( < id > * < id > ) )
< id > := < id > * ( < id > + ( < id > * A ) )
< id > := < id > * ( < id > + ( C * A ) )
< id > := < id > * ( B + ( C * A ) )
< id > := A * ( B + ( C * A ) )
A := A * ( B + ( C * A ) )